Planowanie strategiczne w przedsiębiorstwach handlowych - Lew, Grzegorz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
At present when mercantile enterprises plan to take actions their short-term decisions should be based upon strategic planning. The article presents the ideas of strategic planning of enterprises and the strategies which should be taken into account while strategic planning. The conclusion concerns the proper link between short-term decisions and long-term plans in order to manage the enterprise properly. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 187-191